2003
DOI: 10.1007/s00439-003-0960-2
|View full text |Cite
|
Sign up to set email alerts
|

Sequence variation in the CHAT locus shows no association with late-onset Alzheimer's disease

Abstract: There is substantial evidence for a susceptibility gene for late-onset Alzheimer's disease (AD) on chromosome 10. One of the characteristic features of AD is the degeneration and dysfunction of the cholinergic system. The genes encoding choline acetyltransferase (ChAT) and its vesicular transporter (VAChT), CHAT and SLC18A3 respectively, map to the linked region of chromosome 10 and are therefore both positional and obvious functional candidate genes for late-onset AD. We have screened both genes for sequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 32 publications
2
34
0
Order By: Relevance
“…In addition, we also found suggestive associations of all 3 SNPs with cognitive function as measured by MMSE score. Originally, Mubumbila et al [12] reported a significant association of the exon 5 SNP in 122 LOAD cases and 112 controls in a French-German population, but it was not confirmed in subsequent studies [3,5,15]. Recently, Kim et al [8] reported a significant association of this SNP among APOE*4 carriers in a Korean sample.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, we also found suggestive associations of all 3 SNPs with cognitive function as measured by MMSE score. Originally, Mubumbila et al [12] reported a significant association of the exon 5 SNP in 122 LOAD cases and 112 controls in a French-German population, but it was not confirmed in subsequent studies [3,5,15]. Recently, Kim et al [8] reported a significant association of this SNP among APOE*4 carriers in a Korean sample.…”
Section: Discussionmentioning
confidence: 99%
“…In a pilot study of 119 AD cases and 116 controls, Harold et al [5] reported significantly lower frequency of the A allele of the intron 9 SNP in AD cases than controls (15% vs. 23 %; p=0.034). In two replication samples, Harold et al [5] found similar but non-significant trend in one sample but not in the other sample.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Cardiff group identified polymorphisms within KIAA0319 through dbSNP or by denaturing highperformance liquid chromatography as previously described, 28 while the Oxford group selected new markers that were located within multi-species conserved sequences (MCSs). 29 SNPs with a minor allele frequency < 5% were included if they were of putative functional significance (e.g.…”
Section: Genotypingmentioning
confidence: 99%